A ZAP‐70 kinase domain variant prevents thymocyte‐positive selection despite signalling CD69 induction. Issue 4 (April 2014) - Siggs, Owen M.; Yates, Adèle L.; Schlenner, Susan; Liston, Adrian; Lesage, Sylvie; Goodnow, Christopher C.
Summary Quantitative reductions in T‐cell receptor (TCR) signalling are associated with severe immunodeficiency, yet in certain cases can lead to autoimmunity. Mutation of the tyrosine kinase ZAP‐70 can cause either of these outcomes, yet the limits of its signal transducing capacity are not well defined. To investigate these limits we have made use of mrtless: a chemically induced mutation of Zap70 associated with T‐cell deficiency. Unlike cells devoid of ZAP‐70, mrtless thymocytes showed partial induction of CD5 and CD69, and were sensitive to TCR stimulation with a dose–response shifted approximately 10‐fold. However, essentially no T cells were able to compensate for the mrtless mutation and mature beyond the CD4+ CD8+ stage. This outcome contrasts with a ZAP‐70 Src Homology 2 domain mutant strain, where high‐affinity self‐reactive TCR are positively selected rather than deleted. We discuss these data with respect to current models of TCR signalling in thymocyte selection.